2015
DOI: 10.1002/chem.201500096
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Solubility Parameter Correlations of Gelation Abilities for Dihydroxylated Derivatives of Long‐Chain, Naturally Occurring Fatty Acids

Abstract: Creating structure-property correlations at different distance scales is one of the important challenges to the rational design of molecular gelators. Here, a series of dihydroxylated derivatives of long-chain fatty acids, derived from three naturally occurring molecules-oleic, erucic and ricinoleic acids-are investigated as gelators of a wide variety of liquids. Conclusions about what constitutes a more (or less!) efficient gelator are based upon analyses of a variety of thermal, structural, molecular modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…PXRD diffractograms of the neat ammonium ricinelaidates and their 5 wt % fast‐cooled gels in nitrobenzene were also obtained (Figure and Figure S6). When a sufficient number of diffraction peaks were available, cell constants and Bragg spacings ( d ) of the neat gelators were calculated (Table ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PXRD diffractograms of the neat ammonium ricinelaidates and their 5 wt % fast‐cooled gels in nitrobenzene were also obtained (Figure and Figure S6). When a sufficient number of diffraction peaks were available, cell constants and Bragg spacings ( d ) of the neat gelators were calculated (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…In this regard, we have investigated the gelating abilities of a number of long‐chain, naturally‐occurring fatty acids in which minor additions and deletions of functional groups have been introduced . Among them are derivatives and isomers of the well‐known and very efficient fatty acid gelator, ( R )‐12‐hydroxystearic acid ( d ‐12HSA) . Here, we investigate the gelating abilities of ricinelaidic acid ( d ‐REA) and its salts (made with n ‐alkylamines or alkane‐α,ω‐diamines) (Scheme ) and the properties of their gels in a wide range of organic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…[7,10] Naturally occurring fatty acids and their derivatives are available as triglycerides in many plant-seed oils. [13] They have garnered considerable interest recentlya sm olecular gelators [14] becausem any structural modifications are possible, and those changes can be correlated with gelator efficiency.F or example, stearic acid (SA), which contains only one H-bond donation and acceptance site, is av ery inefficient gelator (Scheme 1). [15] Whereas 10-oxooctadecanoic acid (10-KSA), am onoketo derivative,i sarelatively efficient gelatora saresult of its added abilityt oi nitiate intermolecular keto-keto dipolar interactions along the polymethylene chain.…”
Section: Introductionmentioning
confidence: 99%
“…4 The next challenge in the field is to evaluate how small changes in the structure of a LMWG will affect the gelation domain. [27][28][29][30][31][32][33] In particular, we previously probed the influence of the length of an alkyl chain within a family of related gelators, but showed that it is difficult to rationalize the results without knowledge of the molecular packing. 33 To better correlate the molecular structure with the gelation domain, we selected a family of amide-based thiazole derivatives bearing a long aliphatic chain, for which the elucidation of the molecular packing seemed to be within reach ( Figure 1).…”
Section: Several Examples Of Lmwg Have Been Reported In the Literaturmentioning
confidence: 99%